Analisis Potensi Pemungutan PKB Dan BBNKB Dalam Upaya Meningkatkan Penerimaan Pajak Daerah - Francky William Leonardo Lona; Dwikora Harjo (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Regional taxes have several types of tax objects, and the closest to the community, one of which is the Motor Vehicle Tax (PKB) and the Motor Vehicle Title Transfer Fee (BBNKB). The phenomena that exist in this study is that there are still many obstacles that hinder the realization of PKB and BBNKB revenues in certain years not meeting the targets set by the Government, with the 2017 Motor Vehicle Tax revenue only reaching 98.49% and 98.03% for The Title Transfer Fee. Even though in 2018 the Motor Vehicle Tax exceeded the target with 101.10% and the Title Transfer Fee with 104.40%, in 2019 it did not exceed the target again with only 76.56% from the Motor Vehicle Tax and 79.74% for the Title Transfer Fee. Meanwhile, registered motor vehicles continue to increase every year. This study was conducted to analyze the potential for motor vehicle tax and motor vehicle title transfer fee in an effort to increase regional tax revenue at the Samsat Atambua Joint Office, Belu Regency, East Nusa Tenggara Province from 2017 to 2019. In this study, the researcher used Kenneth Davey's potential theory. According to him, in order to assess the potential and performance of a type of levy, criteria are needed. They are adequacy and elasticity, fairness, administrative capacity, political agreement, economic efficiency, and suitability as regional levies. The approach used in this study was a qualitative approach with descriptive methods. The data collection in this study was by observation, documentation, and interviews. The results of this study indicated that the potential for motor vehicle tax and title transfer fee did not reach the target in certain years was due to several obstacles experienced by the Samsat Atambua Joint Office, such as minimal infrastructure, the lack of public awareness, and low knowledge of motor vehicle tax and title transfer fee.